Comparison Analysis of Optimal Portfolio Formation on Jakarta Islamic Index 70 (JII70) (Markowitz Model and Single Index Model Approach) - Anwar, Indah Lestari; Damang, Kasman; Pakki, Erlina (Advances in Social Sciences Research Journal, 2022)
This study analyzes the optimal portfolio formation of Islamic stocks on Jakarta Islamic Index 70 (JII70) with the Markowitz and Single Index models. The analysis then compares the proportion of funds, return, and portfolio risk. The subsequent analysis compares the two models’ optimal and non-optimal returns and risks. This study uses data on stock prices, dividends, BI-7 Day Reverse Repo Rate, and Composite Stock Price Index for May 2018-September 2021. The research sample is 37 JII70 stock issuers obtained by the purposive sampling technique. The Markowitz model produces 12 combinations, a certain expected return of 0.66% and the best portfolio risk of 3.22%. In comparison, the Single Index Model produces nine stock combinations, the best-expected return of 2.28%, and a certain portfolio risk of 7.53%. Analysis with the Markowitz Model shows no significant difference between stock returns included in the optimal and non-optimal portfolio. However, there is a significant difference between stock risk. In addition, in the Single Index Model, it was found that there was a significant difference between stock returns, including optimal and non-optimal portfolios. However, there was no significant difference between stock risk. The study results can be an essential reference for JII70 investors and stakeholders before and during the Covid-19 pandemic in Indonesia.